FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB BAYAR PAJAK PADA PAJAK KENDARAAN BERMOTOR - Dheviera Agung Pramesty; Mohammad Eddy Rosyadi (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study was to find out the factors that affect taxpayer compliance with motor vehicle taxes. The data used in the study used primary data sourced from questionnaires that had been disseminated to respondents. For sampling using nonprobability sampling technique, accidental sampling as many as 200 respondents. The population used in this study is all taxpayers of two-wheeled motor vehicles registered with the Samsat Office of Bekasi City. The analytical method used in this study used multiple linear regression analysis. The results of this study show that taxpayer awareness, tax access, quality of service, tax sanctions, and tax knowledge influence taxpayer compliance with motor vehicle taxes. While moral obligations have no effect on taxpayer compliance with motor vehicle taxes. Based on the results of the study, it can be explained that the increase in compliance of motor vehicle taxpayers in The City of Bekasi is inseparable from taxpayer awareness, tax access, quality of service, tax sanctions, and tax knowledge. As for moral obligations due to lack of understanding related to moral obligations contained in a person such as having ethics, principles, feelings of guilt or feeling anxious if they do not meet their tax obligations